2005
DOI: 10.1179/174367606x69870
|View full text |Cite
|
Sign up to set email alerts
|

Crystallisation of processed nepheline syenite–magnesite glasses

Abstract: Transparent glasses were prepared from processed nepheline syenite-magnesite mixtures. Incorporation of TiO 2 in the base glasses changes the glass colour from white to amber or dark brown. Translucent porcelainous glass ceramics with white, creamy and a variety of bluish colorations were obtained in glasses containing non-magnetic nepheline syenite. However, dark marblelike glass ceramics were developed in glasses containing middling and tailing nepheline syenite. Aluminium diopside [Ca(Mg,Al)(Si,Al) 2 O 6 ],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Thus, the residual glass would be located in the region of formation of gehlenite phase, which is a silicate belonging to the melilite group. Concerning to augite (pyroxene group) devitrification, several studies have shown that the incorporation of TiO 2 in the base glass not only facilitates early devitrification but it also enhances the development of crystalline phases belonging to the pyroxene group [17]. Both melilite and augite are common crystalline phases in glass ceramics prepared from wastes vitrification [23][24][25][26] and basalt glasses [27] and they lead to glass-ceramics with potential application in the building material industry [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the residual glass would be located in the region of formation of gehlenite phase, which is a silicate belonging to the melilite group. Concerning to augite (pyroxene group) devitrification, several studies have shown that the incorporation of TiO 2 in the base glass not only facilitates early devitrification but it also enhances the development of crystalline phases belonging to the pyroxene group [17]. Both melilite and augite are common crystalline phases in glass ceramics prepared from wastes vitrification [23][24][25][26] and basalt glasses [27] and they lead to glass-ceramics with potential application in the building material industry [28].…”
Section: Discussionmentioning
confidence: 99%
“…This behaviour indicates that the devitrification process of RHA glass will primarily occur through a surface crystallization mechanism. Normally, nepheline glass-ceramics are produced by controlled heat treatments in two steps (nucleation and crystal growth) from bulk glasses whose composition includes nucleating agents as TiO 2 [33,34]. If this surface crystallization mechanism will be confirmed, glass-ceramics at lower temperatures and without the use of nucleating agent could be obtained through a sintering route.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have been mostly focused on glass in systems like SiO2-Al2O3 , MgO-Al2O3-SiO2, and CaO-Al2O3-SiO2 [5]. In order to avoid uncontrolled crystallizing, controlled surface crystallizing has been performed on glasses in systems MgO-Al2O3-SiO2 and CaO-Al2O3-SiO2 [6]. The basic phases of crystalline have been found to be anorthite (CaAl2Si2O8), titanite (CaTiSiO5), wollastonite (CaSiO3), spinel (MgAl2O4) forsterite (Mg2SiO4), and cordierite ((Mg, Fe)2Al4Si5O18), [6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid uncontrolled crystallizing, controlled surface crystallizing has been performed on glasses in systems MgO-Al2O3-SiO2 and CaO-Al2O3-SiO2 [6]. The basic phases of crystalline have been found to be anorthite (CaAl2Si2O8), titanite (CaTiSiO5), wollastonite (CaSiO3), spinel (MgAl2O4) forsterite (Mg2SiO4), and cordierite ((Mg, Fe)2Al4Si5O18), [6]. Research on CaO-MgO-Al2O3-SiO2 system is significant as well in order to understand the reaction that occurs in the rocks, MgO refractories, and blast furnace slag [7].…”
Section: Introductionmentioning
confidence: 99%